The Absence as Presence: A Navigation of Space and Darkness in Mark Z. Danielewski’s Ergodic Novel House of Leaves - Catharinal Silvia M (ILN Journal: Indian Literary Narratives, 2024)
Mark Z. Danielewski's ergodic novel, House of Leaves, intricately employs various narrative techniques to represent the thematic presence of absence and space in the novel. The novel navigates through layers of darkness and space structures that challenge traditional notions of storytelling. Within the unconventional format of the novel, the exploration of space transcends physical boundaries, delving into psychological and existential dimensions, and altering spatiotemporal realities in both the plot and text. Conclusively, through extensive analysis of the interplay between absence and darkness in House of Leaves, this study exposes Danielewski’s intended meaning that human knowledge shrinks time and space.